Calorimetry triggering in ATLAS - Anduaga, Xabier Sebastián (2009)
The ATLAS experiment is preparing for data taking at 14 TeV collision energy. A rich discovery physics program is being prepared in addition to the detailed study of Standard Model processes which will be produced in abundance. The ATLAS multi-level trigger system is designed to accept one event in 2 105 to enable the selection of rare and unusual physics events. The ATLAS calorimeter system is a precise instrument, which includes liquid Argon electro-magnetic and hadronic components as well as a scintillator-tile hadronic calorimeter. All these components are used in the various levels of the trigger system. A wide physics coverage is ensured by inclusively selecting events with candidate electrons, photons, taus, jets or those with large missing transverse energy. The commissioning of the trigger system is being performed with cosmic ray events and by replaying simulated Monte Carlo events through the trigger and data acquisition system.